Ten tips for statistical educators in response to a constructive review of the book How to Analyze Data - MacDougall, Margaret (Journal of University Teaching and Learning Practice, 2021)
This paper comprises a review of the Pocket Study Skills book How to Analyze Data which I was invited by MacMillan International Higher Education to provide as a contribution to the current special issue. This includes both a preliminary review and an extension of this review to provide ten tips for educators to enhance the statistical learning of non-specialists in statistics. The tips are intended to provide a constructive approach to the review process through safeguarding educators, including dissertation supervisors, and learners, from being misled by some of the shortcomings that I have identified in this book. It is in this sense that I refer to these tips as “remedial tips”. As such, these tips should not be regarded as exhaustive in their own right in reflecting the statistical learning needs of non-specialists. Nevertheless, one of the important responsibilities professionally trained statisticians face in the teaching of statistics to non-specialists is that of empowering learners to stem the tide of misuse of statistics within their own disciplines, and one of the corresponding challenges is that of identifying published material that is potentially unhelpful and even counterproductive in achieving this goal. Thus, it is also my intention that these tips will be of broader pedagogical value as a handy reference, including for those uninitiated teachers of statistics to non-specialists who may be tempted to reach out for a pocket guide to support them in balancing the demands of teaching and research in an effort to make statistics less mystifying to their students.